The twilight of Nigerian '419' fraudsters - Okagbare, B. C. (Lagos, Nigeria : Mbeyi & Associates (Nig) Ltd., 2003)
A chronicle of of the neferarious activities of a group of Nigerians running the economy and corporate image of Nigerian citizens aground - 419ers. Explains their activities in plain language for the layman to understand and convince the populace to fight the evil.
Includes index.
oif 23/02/15
Loan
Keywords: Swindlers and swindling -- Nigeria; Corruption -- Nigeria..; Fraud -- Nigeria; Crime -- Nigeria